Article PENGARUH PEMBELAJARAN DENGAN LEARN FROM HOME TERHADAP HASIL BELAJAR MAHASISWA DI STKIP SYEKH MANSHUR: PENGARUH PEMBELAJARAN DENGAN LEARN FROM HOME TERHADAP HASIL BELAJAR MAHASISWA - Usep Saepul Mustakim (Cakrawala Pedagogik, 2020)
Learning with learn from home is carried out because of the current conditions in the midst of the Covid-19 pandemic which makes policies from institutions which also refer to the above policy that learning must continue to be carried out without face-to-face with maximum learning outcomes. This study aims to determine the learning outcomes of students at STKIP Syekh Manshur with learning carried out at home by the lecturer to the students. The test method used in this research is a quantitative descriptive approach with primary data from the accumulated tests at each meeting. After the data were obtained and analyzed with regression analysis assisted by using the SPSS 16 for windows application. The learning outcomes of students by studying at home from this study were obtained by 52% with the results classified as quite good and had a positive impact from this learning.